Electronic records storage system for dynamic business organizations / Nur Amirah Izzati Razali, Nordiana Mohd Nordin and Azman Mat Isa - Razali, Nur Amirah Izzati; Mohd Nordin, Nordiana; Mat Isa, Azman (Universiti Teknologi MARA, Kedah, 2019)
Electronic Records Storage System (eRSS) is an information system that facilitates the management of semi-active records which usually ended up becoming liability and costly to organizations. It is more than usual that loads of semi-active records and undecided documents stored a filing room without proper attention until they are hardly retrievable. A filing room should not be swamped by enormous unmanaged records. Indeed, they are assets that must be managed in a proper way until final legal destruction. Organizations will only realise their importance when a disaster strikes, such as failure to grasp business opportunity or worse ended up facing legal actions as a consequence of poor decision making due to unavailability of accurate and trustworthy information. This mishap can be avoided should semi-active records are properly managed. eRSS was developed based on real world experience. eRSS allows users to create, edit and organize records as they wish to suit the nature of organization. Apart from fundamental records management features, eRSS also allows users to add attachment, long text notes, check boxes, link to other tables and also application of barcodes and QR codes. Another significant feature of eRSS is its ability to alert records manager that appraisal and disposal process is due. Arguably, it is appraisal and disposal of records ensure that records storage room remains conducive and manageable. Semi-active records will be made available whenever required by the management for decision making purpose. Therefore, organizations will benefit smooth business operation and decision which allows the organization to sustain in highly competitive global industry.